Letter (copy) : Clothing for Spain - Tewson, Vincent
028-0086-001 St/H HVT/CB. Secretary's 21st January, 1937. Mr. J. Stolz, International Federation of Trade Unions, 9, Avenue D'Orsay, Paris, VII. Dear Mr. Stolz, Clothing for Spain. I have your letter of the 10th instant, in regard to the above. I am afraid that there was some misunderstanding, occasioned by my speaking over the telephone. The real point I had in mind is that whilst women in this country are knitting garments, it might be advisable for rolls of cotton and cloth to be sent to Spain, to be made up there - as it is so much quicker to sew a simple garment than to knit one. My point was not that the knitting should be done in Spain, instead of in England, but rather that in order to supplement the knitting which is being done here, the refugees themselves might like to have materials for sewing. Yours sincerely, Assistant Secretary. 292/946/28/86